"Comparison of Nissen Rossetti and Floppy Nissen techniques in laparoscopic reflux surgery". (31st December 2023) - Parsak, Cem Kaan; Halvacı, İlker; Topal, Uğur
Abstract: Objective: The present study makes a comparative assessment of the Floppy–Nissen (FN) and Nissen–Rossetti fundoplication (NRF) procedures. Methods: Included in the study were 80 patients who presented to the General Surgery Department outpatient clinic of Balcalı Hospital of the Cukurova University Faculty of Medicine with gastroesophageal reflux between March 2010 and March 2013 All patients were operated on by the same surgeon using the laparoscopic FN or NRF techniques in a randomized controlled manner. The preoperative and postoperative reflux-specific and nonspecific gastrointestinal symptoms of the patients were compared. Results: The duration of symptoms had no effect on the level of satisfaction; regurgitation, bloating and heartburn were more common in those with a longer duration of symptoms Of the patients, 92.5% were satisfied with their resulting condition, and 92.5% were inclined toward the surgery. It was further found that there was no difference between the symptoms or satisfaction levels of the patient groups who underwent the FN procedure and those who underwent the NRF procedure, other than those related to the duration of surgery. laparoscopic NF and the NRF fundoplication treatments, aside from the duration of surgery. Conclusion: Our study revealed no significant difference between the laparoscopic NF and the NRF fundoplication treatments, aside from the duration of surgery. KEY MESSAGES: The Nissen–Rossetti technique can be used safely based on the similarity of its outcomes with those of the classical Nissen technique. Despite the documented success of laparoscopic anti-reflux surgery, the absence of studies comparing surgery and medical treatments prevents these discussions from being concluded. Comparison of Nissen Rossetti and Floppy Nissen Techniques in Laparoscopic Reflux Surgery